THE INFLUENCE OF DIGITAL MARKETING, BRAND AWARENESS, AND EMOTIONAL DESIRE ON MCDONALD'S PURCHASING DECISIONS - Ruhu, Yholand F; Fanggidae, Apriana H. J; Riwu, Yonas Ferdinand; Amtiran, Paulina Y. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to test and analyze the influence of digital marketing, brand awareness and emotional desire on McDonald's purchasing decisions in Kupang City. In this study, the three variables are integrated simultaneously to analyze how digital marketing, brand awareness and emotional desire drive McDonald's purchasing decisions in Kupang City. This study uses a quantitative approach with a survey method. Data were collected through an online questionnaire using a Google form with a Likert scale of 1-5 from 150 respondents. The results of the study indicate that digital marketing, brand awareness, and emotional desire have a positive and significant effect on purchasing decisions. This study is limited to a sample that only includes consumers in the Kupang City area, so the findings cannot be generalized widely to other areas that may have different market characteristics, consumer preferences, or purchasing power levels. The contribution of this study can be a practical reference for fast food business actors in designing strategies that integrate digital marketing, brand awareness, and emotional desire optimally to increase consumer purchasing decisions in the Eastern Indonesia market.